Intermittent fasting from dawn to sunset for 30 consecutive days is associated with anticancer proteomic signature and upregulates key regulatory proteins of glucose and lipid metabolism, circadian clock, DNA repair, cytoskeleton remodeling, immune system and cognitive function in healthy subjects - Mindikoglu, Ayse L.; Abdulsada, Mustafa M.; Jain, Antrix; Choi, Jong Min; Jalal, Prasun K.; Devaraj, Sridevi; Mezzari, Melissa P.; Petrosino, Joseph F.; Opekun, Antone R.; Jung, Sung Yun (Journal of proteomics, 2020)
Murine studies showed that disruption of circadian clock rhythmicity could lead to cancer and metabolic syndrome. Time-restricted feeding can reset the disrupted clock rhythm, protect against cancer and metabolic syndrome. Based on these observations, we hypothesized that intermittent fasting for several consecutive days without calorie restriction in humans would induce an anticarcinogenic proteome and the key regulatory proteins of glucose and lipid metabolism. Fourteen healthy subjects fasted from dawn to sunset for over 14 h daily. Fasting duration was 30 consecutive days. Serum samples were collected before 30-day intermittent fasting, at the end of 4th week during 30-day intermittent fasting, and one week after 30-day intermittent fasting. An untargeted serum proteomic profiling was performed using ultra high-performance liquid chromatography/tandem mass spectrometry. Our results showed that 30-day intermittent fasting was associated with an anticancer serum proteomic signature, upregulated key regulatory proteins of glucose and lipid metabolism, circadian clock, DNA repair, cytoskeleton remodeling, immune system, and cognitive function, and resulted in a serum proteome protective against cancer, metabolic syndrome, inflammation, Alzheimer's disease, and several neuropsychiatric disorders. These findings suggest that fasting from dawn to sunset for 30 consecutive days can be preventive and adjunct therapy in cancer, metabolic syndrome, and several cognitive and neuropsychiatric diseases. Our study has important clinical implications. Our results showed that intermittent fasting from dawn to sunset for over 14 h daily for 30 consecutive days was associated with an anticancer serum proteomic signature and upregulated key regulatory proteins of glucose and lipid metabolism, insulin signaling, circadian clock, DNA repair, cytoskeleton remodeling, immune system, and cognitive function, and resulted in a serum proteome protective against cancer, obesity, diabetes, metabolic syndrome, inflammation, Alzheimer's disease, and several neuropsychiatric disorders. Importantly, these findings occurred in the absence of any calorie restriction and significant weight loss. These findings suggest that intermittent fasting from dawn to sunset can be a preventive and adjunct therapy in cancer, metabolic syndrome and Alzheimer's disease and several neuropsychiatric diseases. [Display omitted] •First human serum proteomics study of 30-day intermittent fasting from dawn to sunset in healthy subjects•The 30-day intermittent fasting from dawn to sunset is associated with a serum proteome protective against cancer•Intermittent fasting from dawn to sunset for 30 days upregulates proteins protective against obesity, diabetes, and metabolic syndrome•Intermittent fasting from dawn to sunset for 30 days induces key regulatory proteins of DNA repair and immune system•Intermittent fasting from dawn to sunset for 30 days upregulates proteins protective against Alzheimer’s disease and neuropsychiatric disorders